2018
DOI: 10.1590/1980-5373-mr-2017-0321
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Electrochemical behaviour of Aluminium Alloy Composites Produced Using Different Sintering Techniques

Abstract: Present research work analyses the effect of heating modes on the densification, microstructure and mechanical properties of aluminum alloys [65Al-20Cu-15Mn] fabricated through powder metallurgy route. Sintering of compacts using conventional, microwave and spark plasma sintering methods has been carried out at 525°C. From the results, it has been observed that the spark plasma sintering method produced the samples with better mechanical properties than the other two methods, followed by microwave and conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Telah banyak penelitian tentang pengujian material radiator [8,9,10], yang menarik [8] melakukan penelitian pada material radiator, bahwa penambahan tembaga pada aluminum akan meningkatkan kekerasan material. Hal ini menunjukkan bahwa setiap radiator memiliki spesifikasinya masing-masing dan mempengaruhi kualitas radiator.…”
Section: Pendahuluanunclassified
“…Telah banyak penelitian tentang pengujian material radiator [8,9,10], yang menarik [8] melakukan penelitian pada material radiator, bahwa penambahan tembaga pada aluminum akan meningkatkan kekerasan material. Hal ini menunjukkan bahwa setiap radiator memiliki spesifikasinya masing-masing dan mempengaruhi kualitas radiator.…”
Section: Pendahuluanunclassified
“…The addition of aluminum in Ni-Ti alloy researched by Pavel Salvetr et al showed the decrease of porosity and improvement of corrosion resistance and hardness [33]. Aluminum (Al) addition is due to its distinctive characteristics, such as low density (2.7 g/cm 3 ) and combination of moderate strength and high ductility, thermal conductivity, electric conductivity, corrosion-resistance [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum is one of the most commonly used metals in modern industry [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Aluminum alloys with a high magnesium content are very popular multifunctional alloys, and are used in the automotive industry, shipbuilding, aerospace engineering and the packaging industry [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%